البعد التّداوليّ وإشكاليّة التّواصل في الثّقافة الشعبيّة مقاربة من منظور سيمياء الثّقافة - عبد الرزاق, بن دحمان (جامعة الوادي - University of Eloued, 2021)
ملخص: تحاول هذه الورقة البحثية دراسة المكون الثقافي للموروث الشعبي من منظور سيمياء الثقافة، وهذا بالوقوف عند إشكالية التداول والتواصل بين وسائط الحضور الفعلي للكتابة ذات البعد الجماهيري والتأصيل المرجعي للكتابة ذات التكوّن النخبوي . الإشكال المعرفي المطروح في هذا المقام هو كيف يمكن بناء ثقافة شعبية تؤسس لتخييل مرجعي قادر على تكوين ثقافة راسخة لها حضورها التداولي ،وتكون بذلك وسيطا بين ثقافة النخبة وثقافة الجماهير ، ولطرح هذه المواقف حاولنا استحضار منظومة " سيمياء الثقافة " في بعدها الاجتماعي محاولة لفهم الثقافة الاجتماعية والكيفية التي تترسخ بها مجموع القيم والأفكار لدى الأفراد والجماعات. Abstract: This article attempts to study the cultural component of popular heritage from the point of view of semiotics of culture, and it is to stop at the problem of trade and communication between the media of the actual presence of writing with a mass dimension and the reference rooting of writing with an elitist composition. The cognitive problem presented here is how to build a popular culture that establishes a reference imagination capable of creating a well-established culture it has its trade presence, it being a media between the culture of the elite and the culture of the masses, and to highlight these positions, we tried to evoke the system of "semiotics of culture" in its social dimension in an attempt to understand social culture and how the sum of values and ideas are Anchoring in people and groups.
مقال
Keywords: الكلمات المفتاحية / التخييل، التواصل، النخبة، التداول، سيمياء الثقافة; Keywords/Imagination, Communication, Elite, Trading, semiotics of cultur